MENGELOLA “VIRTUAL TEACHINGPLACE” BAGI GURU SEKOLAH DASAR (SD) DALAM PROSES MENGAJAR DI MASA PADEMI VIRUS COVID 19 SEMESTER DUA TAHUN 2021 - Sutan Saribumi Pohan (Program Studi Pendidikan Sejarah - Universitas Samudra, 2021)
Elementary school (SD) as the beginning of children getting to know learning at school with teachers and their peers is a place to socialize and get to know the environment in the corridor of education. Competency for students at the level of elementary school age (SD) which begins with the learning process in class is a vehicle to develop students' talents, character, and intelligence to reach their goals in the future before adulthood. In theory, the learning process for students is a series of mental and physical activities to obtain a change in behavior as a result of individual experiences in interaction with their environment which is oriented towards cognitive, affective, and psychomotor (Syaiful Bahri, 2002 p. 13). In early 2020, the country of Indonesia and even the world was hit by an outbreak of the coronavirus and covid 19, which until the beginning of 2021 the virus had not subsided, even the level of transmission was getting higher, resulting in the learning process in schools (class) switching to learning at home via the internet (online) virtually. The role of the teacher has also shifted from teaching in the classroom to virtual teaching or webinars via the internet so that the learning process depends on the media of computers, laptops, and gadgets (HP). The teacher's role in the teaching process is oriented towards computer applications and in managing the class into a virtual teaching place.